Ideal Cardiovascular Health in Young Adult Populations From the United States, Finland, and Australia and Its Association With cIMT: The International Childhood Cardiovascular Cohort Consortium. Issue 3 (19th June 2013) - Oikonen, Mervi; Laitinen, Tomi T.; Magnussen, Costan G.; Steinberger, Julia; Sinaiko, Alan R.; Dwyer, Terence; Venn, Alison; Smith, Kylie J.; Hutri‐Kähönen, Nina; Pahkala, Katja; Mikkilä, Vera; Prineas, Ronald; et al.
Abstract : Background: Goals for cardiovascular (CV) disease prevention were set by the American Heart Association in 2010 for the concept of CV health. Ideal CV health is defined by 7 CV health metrics: blood pressure, glucose, cholesterol, body mass index, and physical activity on recommended levels; nonsmoking; and a healthy diet. We studied the prevalence of ideal CV health and its associations with ultrasonographically measured carotid intima‐media thickness (cIMT) cross‐sectionally in 5 international populations. Methods and Results: Prevalence of ideal CV health was assessed among 5785 young adults (age, 36.6±3.2 years) comprising 335 participants from the Minneapolis Childhood Cohort Studies (Minnesota), 723 from the Princeton Follow‐up Study, 981 from the Bogalusa Heart Study (BHS), 1898 from the Cardiovascular Risk in Young Finns Study (YFS), and 1848 from the Childhood Determinants of Adult Health Study (CDAH). Only 1% of the participants had all 7 ideal CV health metrics. The number of ideal CV health metrics associated inversely with cIMT in the 4 cohorts in which cIMT was available: for each additional ideal CV health metric, cIMT was 12.7 μm thinner in Minnesota ( P =0.0002), 9.1 μm thinner in BHS ( P =0.05), 10.4 μm thinner in YFS ( P <0.0001), and 3.4 μm thinner in CDAH ( P =0.03). Conclusions: The number of ideal CV health metrics was inversely associated with cIMT in the cohorts in which cIMT was available, indicating that ideal CV health metrics are associated with vascular health at the population level. Ideal CV health was rare in this large international sample of young adults, emphasizing the need for effective strategies for health promotion.